PENDEKATAN ARSITEKTUR SIMBIOSIS TERHADAP SENTRA HASIL PERIKANAN DI DESA SUNGAI KAKAP, KALIMANTAN BARAT - Vivianty, Monica; Sutisna, Sutarki (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
Sungai Kakap Village is a village located on the banks of the Kakap River and directly adjacent to the Natuna Sea, making Sungai Kakap Village famous for its tourism, especially in terms of seafood cuisine and natural scenery for the people of Pontianak City. The issue of seafood restaurants located in the Sungai Kakap Village pier area does not reprocess food waste (especially fish) by throwing it directly into the river. The auction place and fish market also produce waste from leftover fish pieces which then end up in the river. The river water smells bad due to the decomposition of fish protein. The aim of the project is to design an integration so that the Sungai Kakap Village pier area fulfills its potential to rise. The design method applied is "Symbiosis" in order to create a program that integrates the life cycle and activities in the area around the Sungai Kakap Village pier. The program is related to fish auctions, fish markets, fish waste management as well as educational tourism. Fish waste management as a regenerative system in buildings, where fish waste is reprocessed into fuel for fishing boats, namely biodiesel. The benefits of the project are based on the vision of “From Fish, For Fish” which is the basis of the regenerative system which helps preserve fish life in the river ecosystem and becomes the prosperity of the surrounding community. Keywords: ecosystem; fish; kakap; pier; river Abstrak Desa Sungai Kakap merupakan desa yang terletak di tepian Sungai Kakap dan berbatasan langsung dengan Laut Natuna menjadikan Desa Sungai Kakap terkenal akan wisatanya terutama dalam hal kuliner seafood dan pemandangan alamnya bagi masyarakat Kota Pontianak. Isu rumah makan seafood yang berada di area dermaga Desa Sungai Kakap tidak mengolah kembali limbah sisa makanan (terutama ikan) dengan membuangnya langsung ke sungai. Tempat pelelangan dan pasar ikan juga turut menghasilkan limbah dari sisa potongan ikan yang kemudian, berakhir di sungai. Air sungai berbau tidak sedap akibat dekomposisi protein ikan. Tujuan proyek ialah untuk merancang sebuah integrasi agar area dermaga Desa Sungai Kakap memenuhi potensinya untuk menjulang. Metode perancangan yang diterapkan ialah “Simbiosis” agar tercipta sebuah program yang mengintegrasi siklus kehidupan dan aktivitas di area sekitar dermaga Desa Sungai Kakap. Program terkait dengan pelelangan ikan, pasar ikan, manajemen limbah ikan sekaligus eduwisata. Manajemen limbah ikan sebagai sistem regeneratif dalam bangunan, di mana limbah ikan diolah kembali menjadi bahan bakar untuk kapal nelayan, yakni biodiesel. Manfaat proyek berangkat dari visi “From Fish, For Fish” yang menjadi dasar sistem regeneratif turut melestarikan kehidupan ikan di ekosistem sungai serta menjadi kemakmuran komunitas warga sekitar.